Application of Methanol Absorbent for CO2 Removal in Gas-Liquid Hollow Fiber Membrane Contactors - Atashi, H.; Mahdavian, M.; Zivdar, M.; Mousavi, S.M. (Asian Journal of Chemistry, 2012)
In the present work, the physical absorption of CO2 from CO2/CH4 mixture using methanol absorbent was explored by neglecting the reaction term in the model equations. In order to calculate the rates of mass transfer through the membrane and axial and radial diffusion inside the shell, through the membrane and within the tube side of the membrane contactor, a computational mass transfer model was used. The effects of operating conditions such as liquid velocity, gas velocity and temperature were analyzed. The calculated removal efficiencies were compared with the case that absorbent is water. It is shown that methanol solvent can successfully be used for removal of CO2. It is found that the concentration distribution of CO2 in the gas phase along the fiber length obeys plug flow model whereas in the methanol absorbent deeply affected by the interface concentration of CO2, absorbent velocity and CO2 diffusivity. Relative absorption rate of CO2 using methanol absorbent is in the range of 2.2 to 4.6 in comparison with the case of water absorbent. When the absorbent velocity is increased or gas velocity is decreased, CO2 concentration decreases, but the concentration changes aren't the same for equally velocity step size in both gas and absorbent. The model results showed that gas velocity has small effect on liquid phase CO2 concentration.